Penyuluhan dan Pemberian Makanan Tambahan Pada Ibu Hamil Kurang Energi Kronis - Kurniati Akhfar; Alfiah; Irma Suryani Saleh; Hildayanti (JCS, 2025)
Nutritional problems that often occur in pregnant women are Chronic Energy Deficiency (CED), which can have a negative impact on the health of the mother and fetus. Globally, around one in eight pregnant women experience CED, with a significant prevalence in several regions, including Indonesia. CED in pregnant women can cause nutritional imbalances that lead to complications in childbirth, premature birth, low birth weight (LBW), and neonatal death. One effort to overcome CED is by providing additional food (PMT), which aims to increase the energy and protein intake of pregnant women. This community service aims to increase the knowledge of pregnant women regarding the importance of PMT and to monitor changes in the nutritional status of pregnant women who experience CED. The method used in this community service is counseling regarding CED and PMT for pregnant women at the Ponre Health Center. Before the intervention, nutritional status was measured using the Upper Arm Circumference (LILA). The results showed that after the counseling, there was an increase in the knowledge of pregnant women regarding CED and the benefits of PMT. Although changes in nutritional status have not been seen in a short time, it is hoped that pregnant women and the community can process and consume appropriate food ingredients to improve nutritional adequacy. With the assistance, it is expected that pregnant women can maintain optimal nutritional status for the health of the mother and the baby born.